Dietary hempseed and cardiovascular health: nutritional composition, mechanisms and comparison with other seeds - Kaçar, Ömer Furkan; Kose, Tugba; Kaya Kaçar, Hüsna (Frontiers in Nutrition, 2025)
Cardiovascular disease (CVD) remains the leading cause of global mortality, with dietary habits playing a significant role in its prevention and management. Hempseed (Cannabis sativa L.) has gained recognition as a functional food due to its rich nutritional profile, including high-quality plant proteins, optimal omega-6 to omega-3 fatty acid ratios, and a variety of bioactive compounds such as tocopherols, phytosterols, and polyphenols. This review critically evaluates the potential cardioprotective effects of hempseed, focusing on its impact on lipid metabolism, inflammation, oxidative stress, and other cardiometabolic markers. Preclinical studies suggest that hempseed can improve lipid profiles, reduce blood pressure, and reduce oxidative stress and inflammation, though clinical evidence remains limited and findings from animal models may not directly translate to human cardiovascular benefits due to physiological differences between species. This review further evaluates hempseed’s potential in cardiovascular disease prevention and highlights its potential advantages when compared with other widely consumed seeds (flaxseed and chia seeds), emphasizing its unique fatty acid composition, optimal omega-6 to omega-3 ratio, and diverse bioactive compounds. Despite the promising findings, there is a need for long-term randomized controlled trials to establish the efficacy and safety of hempseed in diverse populations. This review emphasizes the potential of hempseed as a dietary intervention for CVD prevention and calls for further research to optimize its use in clinical and public health settings.